2016
DOI: 10.1373/clinchem.2015.246876
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Temporal Changes in Cardiovascular Biomarker Concentrations Improves Risk Prediction in an Elderly Population from the Community

Abstract: BACKGROUND:There is increasing interest in measurements of cardiovascular (CV) biomarker concentrations for risk prediction in the general population. We investigated the prognostic utility of a panel of novel CV biomarkers including biomarker changes over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The longitudinal evolution of the biomarkers via joint modeling showed a stronger positive association of GDF-15 with death from CHD and HF than the single biomarker measurements. Related to our findings, Eggers et al found that baseline concentrations of GDF-15 could predict future CVD events and especially all-cause mortality in an elderly community-dwelling population [ 26 ]. In detail, changes over the time of GDF-15 predicted individual´s all-cause mortality, whereas GDF-15 and cardiovascular events displayed no significant association [ 26 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The longitudinal evolution of the biomarkers via joint modeling showed a stronger positive association of GDF-15 with death from CHD and HF than the single biomarker measurements. Related to our findings, Eggers et al found that baseline concentrations of GDF-15 could predict future CVD events and especially all-cause mortality in an elderly community-dwelling population [ 26 ]. In detail, changes over the time of GDF-15 predicted individual´s all-cause mortality, whereas GDF-15 and cardiovascular events displayed no significant association [ 26 ].…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, in this community-dwelling cohort with 3,428 participants GDF-15 as well as the other biomarkers soluble ST2 (sST2) and high-sensitivity troponin I (hsTnI) did not predict coronary artery disease events, but total mortality [ 18 ]. Notable, in some of the previous described community-dwelling cohorts participants were elderly individuals with a higher-risk of developing CVD events and HF [ 15 , 17 , 26 ]. In comparison, the Dan-MONICA cohort represents a middle-aged cohort which is more similar to the Dallas Heart Study [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies of associations of protein levels with changes in body weight or fat distribution during aging have typically focused on one or a few proteins and typically on well‐studied biomarkers, such as C‐reactive protein, interleukin‐6, N‐terminal pro‐B‐type natriuretic peptide, and troponin I . In the present study, we evaluated for the first time whether changes of a large number of proteins between ages 70 and 80 were related to changes in measures of body weight and fat distribution during the same time period.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, in HF patients volume overload is frequently associated to other comorbidities, including bad lifestyle, aging, systemic abnormalities (renal impairment for example), but also bad lifestyle, aging. 31 Interestingly, it has been reported in general population that poor health behaviours (smoking habits, inactivity, nutritional disorders …) and presence of modifiable cardiovascular risk factors (high blood pressure, cholesterol, glucose intolerance, and obesity) are associated with high levels of GDF-15. 39 In addition, in a cohort of 324 same-sex twins, it has been shown that half of the variation in GDF-15 could be attributed to individual-specific environmental influences.…”
Section: Additional Values Of Biomarkers Over Timementioning
confidence: 99%